HUBUNGAN BEBAN KERJA DAN PERAN GANDA TERHADAP KESEHATAN MENTAL PEKERJA WANITA MENIKAH : TINJAUAN LITERATUR THE RELATIONSHIP BETWEEN WORKLOAD AND DUAL ROLE CONFLICT ON MENTAL HEALTH OF MARRIED FEMALE WORKERS : LITERATURE REVIEW - Rosa Febriani Putri Dira; ⁠Dani Nasirul Haqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing participation of married women in the workforce has given rise to dual role conflicts that pose significant risks to mental health. This study aims to examine the relationship between workload and dual roles on the mental health of married female workers through a systematic literature review. Literature searches were conducted using Google Scholar and Science Direct databases from January to April 2026, using keywords such as “workload,” “dual role,” “work-family conflict,” “mental health,” “married working women,” and “female workers.” From 2,360 initial results, 11 articles published between 2010 and 2026 met the inclusion criteria. The review findings indicate that workload and dual role conflict have a positive and significant relationship with mental health disturbances in married female workers, including work stress, emotional exhaustion, depression, and burnout. The magnitude of the association varied across studies, with dual role conflict explaining up to 33.8% of the variation in work stress and work-family conflict more than doubling the risk of depressive symptoms (OR = 2.29). One study, however, found no statistically significant relationship between the two variables. Additional moderating factors such as social support, work environment, and organizational policy also play important roles. Married female workers represent a vulnerable group that requires targeted intervention and family-friendly workplace policies to protect their psychological well-being.